Kinerja Keuangan Pemerintah Daerah (Tax Ratio, Tax Base, dan Penerimaan Non Pajak) Indonesia - Nersiwad (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
The research title is the Financial Performance (Tax Ratio, Tax Base, and Non-Tax Revenue) Indonesia 2013-2018. The research objective was to find out about: 1) the performance of government revenue based on the tax ratio, and 2) the potential tax base and non-tax revenue. The research design was descriptive qualitative, which provided time-series data from 2013 to 2018. The results showed that: 1) the tax ratio continued to decline during the period of analysis (2013-2017), but it improved (recovery) in 2018, 2) the rise of tax ratio was prolonged if it was analyzed using the tax base, its development in 2018 decreased than the previous year (2013), and 3) the performance of non-tax revenues significantly increased, where a sharp rise occurred in 2018. The decrease of tax ratio required steps to improve its tax base by improving some sectors, including the small/medium industry and the manufacturing industry, improving tax administration, and reducing delinquencies. Meanwhile, non-tax revenues' performance needs to be maintained to support the total government revenue, mainly revenue from natural resources through improvement, technology, financing, and others.